base-compat-0.11.2: A compatibility layer for base
Safe HaskellSafe-Inferred
LanguageHaskell2010

Control.Monad.Compat

Synopsis

Documentation

guard :: Alternative f => Bool -> f () Source #

Conditional failure of Alternative computations. Defined by

guard True  = pure ()
guard False = empty

Examples

Expand

Common uses of guard include conditionally signaling an error in an error monad and conditionally rejecting the current choice in an Alternative-based parser.

As an example of signaling an error in the error monad Maybe, consider a safe division function safeDiv x y that returns Nothing when the denominator y is zero and Just (x `div` y) otherwise. For example:

>>> safeDiv 4 0
Nothing
>>> safeDiv 4 2
Just 2

A definition of safeDiv using guards, but not guard:

safeDiv :: Int -> Int -> Maybe Int
safeDiv x y | y /= 0    = Just (x `div` y)
            | otherwise = Nothing

A definition of safeDiv using guard and Monad do-notation:

safeDiv :: Int -> Int -> Maybe Int
safeDiv x y = do
  guard (y /= 0)
  return (x `div` y)

join :: Monad m => m (m a) -> m a Source #

The join function is the conventional monad join operator. It is used to remove one level of monadic structure, projecting its bound argument into the outer level.

'join bss' can be understood as the do expression

do bs <- bss
   bs

Examples

Expand

A common use of join is to run an IO computation returned from an STM transaction, since STM transactions can't perform IO directly. Recall that

atomically :: STM a -> IO a

is used to run STM transactions atomically. So, by specializing the types of atomically and join to

atomically :: STM (IO b) -> IO (IO b)
join       :: IO (IO b)  -> IO b

we can compose them as

join . atomically :: STM (IO b) -> IO b

to run an STM transaction and the IO action it returns.

class Applicative m => Monad (m :: Type -> Type) where Source #

The Monad class defines the basic operations over a monad, a concept from a branch of mathematics known as category theory. From the perspective of a Haskell programmer, however, it is best to think of a monad as an abstract datatype of actions. Haskell's do expressions provide a convenient syntax for writing monadic expressions.

Instances of Monad should satisfy the following:

Left identity
return a >>= k = k a
Right identity
m >>= return = m
Associativity
m >>= (\x -> k x >>= h) = (m >>= k) >>= h

Furthermore, the Monad and Applicative operations should relate as follows:

The above laws imply:

and that pure and (<*>) satisfy the applicative functor laws.

The instances of Monad for lists, Maybe and IO defined in the Prelude satisfy these laws.

Minimal complete definition

(>>=)

Methods

(>>=) :: m a -> (a -> m b) -> m b infixl 1 Source #

Sequentially compose two actions, passing any value produced by the first as an argument to the second.

'as >>= bs' can be understood as the do expression

do a <- as
   bs a

(>>) :: m a -> m b -> m b infixl 1 Source #

Sequentially compose two actions, discarding any value produced by the first, like sequencing operators (such as the semicolon) in imperative languages.

'as >> bs' can be understood as the do expression

do as
   bs

return :: a -> m a Source #

Inject a value into the monadic type.

Instances

Instances details
Monad []

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: [a] -> (a -> [b]) -> [b] Source #

(>>) :: [a] -> [b] -> [b] Source #

return :: a -> [a] Source #

Monad Maybe

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: Maybe a -> (a -> Maybe b) -> Maybe b Source #

(>>) :: Maybe a -> Maybe b -> Maybe b Source #

return :: a -> Maybe a Source #

Monad IO

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: IO a -> (a -> IO b) -> IO b Source #

(>>) :: IO a -> IO b -> IO b Source #

return :: a -> IO a Source #

Monad Complex

Since: base-4.9.0.0

Instance details

Defined in Data.Complex

Methods

(>>=) :: Complex a -> (a -> Complex b) -> Complex b Source #

(>>) :: Complex a -> Complex b -> Complex b Source #

return :: a -> Complex a Source #

Monad Min

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Min a -> (a -> Min b) -> Min b Source #

(>>) :: Min a -> Min b -> Min b Source #

return :: a -> Min a Source #

Monad Max

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Max a -> (a -> Max b) -> Max b Source #

(>>) :: Max a -> Max b -> Max b Source #

return :: a -> Max a Source #

Monad First

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: First a -> (a -> First b) -> First b Source #

(>>) :: First a -> First b -> First b Source #

return :: a -> First a Source #

Monad Last

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Last a -> (a -> Last b) -> Last b Source #

(>>) :: Last a -> Last b -> Last b Source #

return :: a -> Last a Source #

Monad Option

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Option a -> (a -> Option b) -> Option b Source #

(>>) :: Option a -> Option b -> Option b Source #

return :: a -> Option a Source #

Monad Identity

Since: base-4.8.0.0

Instance details

Defined in Data.Functor.Identity

Methods

(>>=) :: Identity a -> (a -> Identity b) -> Identity b Source #

(>>) :: Identity a -> Identity b -> Identity b Source #

return :: a -> Identity a Source #

Monad STM

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

(>>=) :: STM a -> (a -> STM b) -> STM b Source #

(>>) :: STM a -> STM b -> STM b Source #

return :: a -> STM a Source #

Monad First

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: First a -> (a -> First b) -> First b Source #

(>>) :: First a -> First b -> First b Source #

return :: a -> First a Source #

Monad Last

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: Last a -> (a -> Last b) -> Last b Source #

(>>) :: Last a -> Last b -> Last b Source #

return :: a -> Last a Source #

Monad Dual

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Dual a -> (a -> Dual b) -> Dual b Source #

(>>) :: Dual a -> Dual b -> Dual b Source #

return :: a -> Dual a Source #

Monad Sum

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Sum a -> (a -> Sum b) -> Sum b Source #

(>>) :: Sum a -> Sum b -> Sum b Source #

return :: a -> Sum a Source #

Monad Product

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Product a -> (a -> Product b) -> Product b Source #

(>>) :: Product a -> Product b -> Product b Source #

return :: a -> Product a Source #

Monad ReadPrec

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

(>>=) :: ReadPrec a -> (a -> ReadPrec b) -> ReadPrec b Source #

(>>) :: ReadPrec a -> ReadPrec b -> ReadPrec b Source #

return :: a -> ReadPrec a Source #

Monad ReadP

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

(>>=) :: ReadP a -> (a -> ReadP b) -> ReadP b Source #

(>>) :: ReadP a -> ReadP b -> ReadP b Source #

return :: a -> ReadP a Source #

Monad NonEmpty

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: NonEmpty a -> (a -> NonEmpty b) -> NonEmpty b Source #

(>>) :: NonEmpty a -> NonEmpty b -> NonEmpty b Source #

return :: a -> NonEmpty a Source #

Monad P

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

(>>=) :: P a -> (a -> P b) -> P b Source #

(>>) :: P a -> P b -> P b Source #

return :: a -> P a Source #

Monad (Either e)

Since: base-4.4.0.0

Instance details

Defined in Data.Either

Methods

(>>=) :: Either e a -> (a -> Either e b) -> Either e b Source #

(>>) :: Either e a -> Either e b -> Either e b Source #

return :: a -> Either e a Source #

Monoid a => Monad ((,) a)

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, a0) -> (a0 -> (a, b)) -> (a, b) Source #

(>>) :: (a, a0) -> (a, b) -> (a, b) Source #

return :: a0 -> (a, a0) Source #

Monad (ST s)

Since: base-2.1

Instance details

Defined in GHC.ST

Methods

(>>=) :: ST s a -> (a -> ST s b) -> ST s b Source #

(>>) :: ST s a -> ST s b -> ST s b Source #

return :: a -> ST s a Source #

Monad (ST s)

Since: base-2.1

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

(>>=) :: ST s a -> (a -> ST s b) -> ST s b Source #

(>>) :: ST s a -> ST s b -> ST s b Source #

return :: a -> ST s a Source #

Monad m => Monad (WrappedMonad m)

Since: base-4.7.0.0

Instance details

Defined in Control.Applicative

Methods

(>>=) :: WrappedMonad m a -> (a -> WrappedMonad m b) -> WrappedMonad m b Source #

(>>) :: WrappedMonad m a -> WrappedMonad m b -> WrappedMonad m b Source #

return :: a -> WrappedMonad m a Source #

Monad (Proxy :: Type -> Type)

Since: base-4.7.0.0

Instance details

Defined in Data.Proxy

Methods

(>>=) :: Proxy a -> (a -> Proxy b) -> Proxy b Source #

(>>) :: Proxy a -> Proxy b -> Proxy b Source #

return :: a -> Proxy a Source #

(Monoid a, Monoid b) => Monad ((,,) a b)

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, b, a0) -> (a0 -> (a, b, b0)) -> (a, b, b0) Source #

(>>) :: (a, b, a0) -> (a, b, b0) -> (a, b, b0) Source #

return :: a0 -> (a, b, a0) Source #

Monad f => Monad (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: Ap f a -> (a -> Ap f b) -> Ap f b Source #

(>>) :: Ap f a -> Ap f b -> Ap f b Source #

return :: a -> Ap f a Source #

Monad f => Monad (Alt f)

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Alt f a -> (a -> Alt f b) -> Alt f b Source #

(>>) :: Alt f a -> Alt f b -> Alt f b Source #

return :: a -> Alt f a Source #

Monad ((->) r :: Type -> Type)

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: (r -> a) -> (a -> r -> b) -> r -> b Source #

(>>) :: (r -> a) -> (r -> b) -> r -> b Source #

return :: a -> r -> a Source #

(Monoid a, Monoid b, Monoid c) => Monad ((,,,) a b c)

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, b, c, a0) -> (a0 -> (a, b, c, b0)) -> (a, b, c, b0) Source #

(>>) :: (a, b, c, a0) -> (a, b, c, b0) -> (a, b, c, b0) Source #

return :: a0 -> (a, b, c, a0) Source #

(Monad f, Monad g) => Monad (Product f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

(>>=) :: Product f g a -> (a -> Product f g b) -> Product f g b Source #

(>>) :: Product f g a -> Product f g b -> Product f g b Source #

return :: a -> Product f g a Source #

class Functor (f :: Type -> Type) where Source #

A type f is a Functor if it provides a function fmap which, given any types a and b lets you apply any function from (a -> b) to turn an f a into an f b, preserving the structure of f. Furthermore f needs to adhere to the following:

Identity
fmap id == id
Composition
fmap (f . g) == fmap f . fmap g

Note, that the second law follows from the free theorem of the type fmap and the first law, so you need only check that the former condition holds.

Minimal complete definition

fmap

Methods

fmap :: (a -> b) -> f a -> f b Source #

Using ApplicativeDo: 'fmap f as' can be understood as the do expression

do a <- as
   pure (f a)

with an inferred Functor constraint.

(<$) :: a -> f b -> f a infixl 4 Source #

Replace all locations in the input with the same value. The default definition is fmap . const, but this may be overridden with a more efficient version.

Using ApplicativeDo: 'a <$ bs' can be understood as the do expression

do bs
   pure a

with an inferred Functor constraint.

Instances

Instances details
Functor []

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> [a] -> [b] Source #

(<$) :: a -> [b] -> [a] Source #

Functor Maybe

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> Maybe a -> Maybe b Source #

(<$) :: a -> Maybe b -> Maybe a Source #

Functor IO

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> IO a -> IO b Source #

(<$) :: a -> IO b -> IO a Source #

Functor Complex

Since: base-4.9.0.0

Instance details

Defined in Data.Complex

Methods

fmap :: (a -> b) -> Complex a -> Complex b Source #

(<$) :: a -> Complex b -> Complex a Source #

Functor Min

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Min a -> Min b Source #

(<$) :: a -> Min b -> Min a Source #

Functor Max

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Max a -> Max b Source #

(<$) :: a -> Max b -> Max a Source #

Functor First

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> First a -> First b Source #

(<$) :: a -> First b -> First a Source #

Functor Last

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Last a -> Last b Source #

(<$) :: a -> Last b -> Last a Source #

Functor Option

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a -> b) -> Option a -> Option b Source #

(<$) :: a -> Option b -> Option a Source #

Functor ZipList

Since: base-2.1

Instance details

Defined in Control.Applicative

Methods

fmap :: (a -> b) -> ZipList a -> ZipList b Source #

(<$) :: a -> ZipList b -> ZipList a Source #

Functor Identity

Since: base-4.8.0.0

Instance details

Defined in Data.Functor.Identity

Methods

fmap :: (a -> b) -> Identity a -> Identity b Source #

(<$) :: a -> Identity b -> Identity a Source #

Functor Handler

Since: base-4.6.0.0

Instance details

Defined in Control.Exception

Methods

fmap :: (a -> b) -> Handler a -> Handler b Source #

(<$) :: a -> Handler b -> Handler a Source #

Functor STM

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

fmap :: (a -> b) -> STM a -> STM b Source #

(<$) :: a -> STM b -> STM a Source #

Functor First

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

fmap :: (a -> b) -> First a -> First b Source #

(<$) :: a -> First b -> First a Source #

Functor Last

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

fmap :: (a -> b) -> Last a -> Last b Source #

(<$) :: a -> Last b -> Last a Source #

Functor Dual

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Dual a -> Dual b Source #

(<$) :: a -> Dual b -> Dual a Source #

Functor Sum

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Sum a -> Sum b Source #

(<$) :: a -> Sum b -> Sum a Source #

Functor Product

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Product a -> Product b Source #

(<$) :: a -> Product b -> Product a Source #

Functor ReadPrec

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

fmap :: (a -> b) -> ReadPrec a -> ReadPrec b Source #

(<$) :: a -> ReadPrec b -> ReadPrec a Source #

Functor ReadP

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fmap :: (a -> b) -> ReadP a -> ReadP b Source #

(<$) :: a -> ReadP b -> ReadP a Source #

Functor NonEmpty

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> NonEmpty a -> NonEmpty b Source #

(<$) :: a -> NonEmpty b -> NonEmpty a Source #

Functor P

Since: base-4.8.0.0

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fmap :: (a -> b) -> P a -> P b Source #

(<$) :: a -> P b -> P a Source #

Functor (Either a)

Since: base-3.0

Instance details

Defined in Data.Either

Methods

fmap :: (a0 -> b) -> Either a a0 -> Either a b Source #

(<$) :: a0 -> Either a b -> Either a a0 Source #

Functor ((,) a)

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a0 -> b) -> (a, a0) -> (a, b) Source #

(<$) :: a0 -> (a, b) -> (a, a0) Source #

Functor (ST s)

Since: base-2.1

Instance details

Defined in GHC.ST

Methods

fmap :: (a -> b) -> ST s a -> ST s b Source #

(<$) :: a -> ST s b -> ST s a Source #

Functor (Arg a)

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

fmap :: (a0 -> b) -> Arg a a0 -> Arg a b Source #

(<$) :: a0 -> Arg a b -> Arg a a0 Source #

Functor (ST s)

Since: base-2.1

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

fmap :: (a -> b) -> ST s a -> ST s b Source #

(<$) :: a -> ST s b -> ST s a Source #

Monad m => Functor (WrappedMonad m)

Since: base-2.1

Instance details

Defined in Control.Applicative

Methods

fmap :: (a -> b) -> WrappedMonad m a -> WrappedMonad m b Source #

(<$) :: a -> WrappedMonad m b -> WrappedMonad m a Source #

Functor (Proxy :: Type -> Type)

Since: base-4.7.0.0

Instance details

Defined in Data.Proxy

Methods

fmap :: (a -> b) -> Proxy a -> Proxy b Source #

(<$) :: a -> Proxy b -> Proxy a Source #

Functor ((,,) a b)

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

fmap :: (a0 -> b0) -> (a, b, a0) -> (a, b, b0) Source #

(<$) :: a0 -> (a, b, b0) -> (a, b, a0) Source #

Arrow a => Functor (WrappedArrow a b)

Since: base-2.1

Instance details

Defined in Control.Applicative

Methods

fmap :: (a0 -> b0) -> WrappedArrow a b a0 -> WrappedArrow a b b0 Source #

(<$) :: a0 -> WrappedArrow a b b0 -> WrappedArrow a b a0 Source #

Functor (Const m :: Type -> Type)

Since: base-2.1

Instance details

Defined in Data.Functor.Const

Methods

fmap :: (a -> b) -> Const m a -> Const m b Source #

(<$) :: a -> Const m b -> Const m a Source #

Functor f => Functor (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

fmap :: (a -> b) -> Ap f a -> Ap f b Source #

(<$) :: a -> Ap f b -> Ap f a Source #

Functor f => Functor (Alt f)

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

fmap :: (a -> b) -> Alt f a -> Alt f b Source #

(<$) :: a -> Alt f b -> Alt f a Source #

Functor ((->) r :: Type -> Type)

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

fmap :: (a -> b) -> (r -> a) -> r -> b Source #

(<$) :: a -> (r -> b) -> r -> a Source #

Functor ((,,,) a b c)

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

fmap :: (a0 -> b0) -> (a, b, c, a0) -> (a, b, c, b0) Source #

(<$) :: a0 -> (a, b, c, b0) -> (a, b, c, a0) Source #

(Functor f, Functor g) => Functor (Product f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

fmap :: (a -> b) -> Product f g a -> Product f g b Source #

(<$) :: a -> Product f g b -> Product f g a Source #

(Functor f, Functor g) => Functor (Sum f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Sum

Methods

fmap :: (a -> b) -> Sum f g a -> Sum f g b Source #

(<$) :: a -> Sum f g b -> Sum f g a Source #

(Functor f, Functor g) => Functor (Compose f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Compose

Methods

fmap :: (a -> b) -> Compose f g a -> Compose f g b Source #

(<$) :: a -> Compose f g b -> Compose f g a Source #

class Monad m => MonadFail (m :: Type -> Type) where Source #

When a value is bound in do-notation, the pattern on the left hand side of <- might not match. In this case, this class provides a function to recover.

A Monad without a MonadFail instance may only be used in conjunction with pattern that always match, such as newtypes, tuples, data types with only a single data constructor, and irrefutable patterns (~pat).

Instances of MonadFail should satisfy the following law: fail s should be a left zero for >>=,

fail s >>= f  =  fail s

If your Monad is also MonadPlus, a popular definition is

fail _ = mzero

Since: base-4.9.0.0

Methods

fail :: String -> m a Source #

Instances

Instances details
MonadFail []

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> [a] Source #

MonadFail Maybe

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> Maybe a Source #

MonadFail IO

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> IO a Source #

MonadFail ReadPrec

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

fail :: String -> ReadPrec a Source #

MonadFail ReadP

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fail :: String -> ReadP a Source #

MonadFail P

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fail :: String -> P a Source #

MonadFail (ST s)

Since: base-4.11.0.0

Instance details

Defined in GHC.ST

Methods

fail :: String -> ST s a Source #

MonadFail (ST s)

Since: base-4.10

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

fail :: String -> ST s a Source #

MonadFail f => MonadFail (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

fail :: String -> Ap f a Source #

mapM :: (Traversable t, Monad m) => (a -> m b) -> t a -> m (t b) Source #

Map each element of a structure to a monadic action, evaluate these actions from left to right, and collect the results. For a version that ignores the results see mapM_.

sequence :: (Traversable t, Monad m) => t (m a) -> m (t a) Source #

Evaluate each monadic action in the structure from left to right, and collect the results. For a version that ignores the results see sequence_.

mfilter :: MonadPlus m => (a -> Bool) -> m a -> m a Source #

Direct MonadPlus equivalent of filter.

Examples

Expand

The filter function is just mfilter specialized to the list monad:

filter = ( mfilter :: (a -> Bool) -> [a] -> [a] )

An example using mfilter with the Maybe monad:

>>> mfilter odd (Just 1)
Just 1
>>> mfilter odd (Just 2)
Nothing

(<$!>) :: Monad m => (a -> b) -> m a -> m b infixl 4 Source #

Strict version of <$>.

Since: base-4.8.0.0

unless :: Applicative f => Bool -> f () -> f () Source #

The reverse of when.

replicateM_ :: Applicative m => Int -> m a -> m () Source #

Like replicateM, but discards the result.

replicateM :: Applicative m => Int -> m a -> m [a] Source #

replicateM n act performs the action n times, gathering the results.

Using ApplicativeDo: 'replicateM 5 as' can be understood as the do expression

do a1 <- as
   a2 <- as
   a3 <- as
   a4 <- as
   a5 <- as
   pure [a1,a2,a3,a4,a5]

Note the Applicative constraint.

foldM_ :: (Foldable t, Monad m) => (b -> a -> m b) -> b -> t a -> m () Source #

Like foldM, but discards the result.

foldM :: (Foldable t, Monad m) => (b -> a -> m b) -> b -> t a -> m b Source #

The foldM function is analogous to foldl, except that its result is encapsulated in a monad. Note that foldM works from left-to-right over the list arguments. This could be an issue where (>>) and the `folded function' are not commutative.

foldM f a1 [x1, x2, ..., xm]

==

do
  a2 <- f a1 x1
  a3 <- f a2 x2
  ...
  f am xm

If right-to-left evaluation is required, the input list should be reversed.

Note: foldM is the same as foldlM

zipWithM_ :: Applicative m => (a -> b -> m c) -> [a] -> [b] -> m () Source #

zipWithM_ is the extension of zipWithM which ignores the final result.

zipWithM :: Applicative m => (a -> b -> m c) -> [a] -> [b] -> m [c] Source #

The zipWithM function generalizes zipWith to arbitrary applicative functors.

mapAndUnzipM :: Applicative m => (a -> m (b, c)) -> [a] -> m ([b], [c]) Source #

The mapAndUnzipM function maps its first argument over a list, returning the result as a pair of lists. This function is mainly used with complicated data structures or a state monad.

forever :: Applicative f => f a -> f b Source #

Repeat an action indefinitely.

Using ApplicativeDo: 'forever as' can be understood as the pseudo-do expression

do as
   as
   ..

with as repeating.

Examples

Expand

A common use of forever is to process input from network sockets, Handles, and channels (e.g. MVar and Chan).

For example, here is how we might implement an echo server, using forever both to listen for client connections on a network socket and to echo client input on client connection handles:

echoServer :: Socket -> IO ()
echoServer socket = forever $ do
  client <- accept socket
  forkFinally (echo client) (\_ -> hClose client)
  where
    echo :: Handle -> IO ()
    echo client = forever $
      hGetLine client >>= hPutStrLn client

(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c infixr 1 Source #

Right-to-left composition of Kleisli arrows. (>=>), with the arguments flipped.

Note how this operator resembles function composition (.):

(.)   ::            (b ->   c) -> (a ->   b) -> a ->   c
(<=<) :: Monad m => (b -> m c) -> (a -> m b) -> a -> m c

(>=>) :: Monad m => (a -> m b) -> (b -> m c) -> a -> m c infixr 1 Source #

Left-to-right composition of Kleisli arrows.

'(bs >=> cs) a' can be understood as the do expression

do b <- bs a
   cs b

filterM :: Applicative m => (a -> m Bool) -> [a] -> m [a] Source #

This generalizes the list-based filter function.

forM :: (Traversable t, Monad m) => t a -> (a -> m b) -> m (t b) Source #

forM is mapM with its arguments flipped. For a version that ignores the results see forM_.

msum :: (Foldable t, MonadPlus m) => t (m a) -> m a Source #

The sum of a collection of actions, generalizing concat. As of base 4.8.0.0, msum is just asum, specialized to MonadPlus.

sequence_ :: (Foldable t, Monad m) => t (m a) -> m () Source #

Evaluate each monadic action in the structure from left to right, and ignore the results. For a version that doesn't ignore the results see sequence.

As of base 4.8.0.0, sequence_ is just sequenceA_, specialized to Monad.

forM_ :: (Foldable t, Monad m) => t a -> (a -> m b) -> m () Source #

forM_ is mapM_ with its arguments flipped. For a version that doesn't ignore the results see forM.

As of base 4.8.0.0, forM_ is just for_, specialized to Monad.

mapM_ :: (Foldable t, Monad m) => (a -> m b) -> t a -> m () Source #

Map each element of a structure to a monadic action, evaluate these actions from left to right, and ignore the results. For a version that doesn't ignore the results see mapM.

As of base 4.8.0.0, mapM_ is just traverse_, specialized to Monad.

void :: Functor f => f a -> f () Source #

void value discards or ignores the result of evaluation, such as the return value of an IO action.

Using ApplicativeDo: 'void as' can be understood as the do expression

do as
   pure ()

with an inferred Functor constraint.

Examples

Expand

Replace the contents of a Maybe Int with unit:

>>> void Nothing
Nothing
>>> void (Just 3)
Just ()

Replace the contents of an Either Int Int with unit, resulting in an Either Int ():

>>> void (Left 8675309)
Left 8675309
>>> void (Right 8675309)
Right ()

Replace every element of a list with unit:

>>> void [1,2,3]
[(),(),()]

Replace the second element of a pair with unit:

>>> void (1,2)
(1,())

Discard the result of an IO action:

>>> mapM print [1,2]
1
2
[(),()]
>>> void $ mapM print [1,2]
1
2

ap :: Monad m => m (a -> b) -> m a -> m b Source #

In many situations, the liftM operations can be replaced by uses of ap, which promotes function application.

return f `ap` x1 `ap` ... `ap` xn

is equivalent to

liftMn f x1 x2 ... xn

liftM5 :: Monad m => (a1 -> a2 -> a3 -> a4 -> a5 -> r) -> m a1 -> m a2 -> m a3 -> m a4 -> m a5 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right (cf. liftM2).

liftM4 :: Monad m => (a1 -> a2 -> a3 -> a4 -> r) -> m a1 -> m a2 -> m a3 -> m a4 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right (cf. liftM2).

liftM3 :: Monad m => (a1 -> a2 -> a3 -> r) -> m a1 -> m a2 -> m a3 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right (cf. liftM2).

liftM2 :: Monad m => (a1 -> a2 -> r) -> m a1 -> m a2 -> m r Source #

Promote a function to a monad, scanning the monadic arguments from left to right. For example,

liftM2 (+) [0,1] [0,2] = [0,2,1,3]
liftM2 (+) (Just 1) Nothing = Nothing

liftM :: Monad m => (a1 -> r) -> m a1 -> m r Source #

Promote a function to a monad.

when :: Applicative f => Bool -> f () -> f () Source #

Conditional execution of Applicative expressions. For example,

when debug (putStrLn "Debugging")

will output the string Debugging if the Boolean value debug is True, and otherwise do nothing.

(=<<) :: Monad m => (a -> m b) -> m a -> m b infixr 1 Source #

Same as >>=, but with the arguments interchanged.

class (Alternative m, Monad m) => MonadPlus (m :: Type -> Type) where Source #

Monads that also support choice and failure.

Minimal complete definition

Nothing

Methods

mzero :: m a Source #

The identity of mplus. It should also satisfy the equations

mzero >>= f  =  mzero
v >> mzero   =  mzero

The default definition is

mzero = empty

mplus :: m a -> m a -> m a Source #

An associative operation. The default definition is

mplus = (<|>)

Instances

Instances details
MonadPlus []

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

mzero :: [a] Source #

mplus :: [a] -> [a] -> [a] Source #

MonadPlus Maybe

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

mzero :: Maybe a Source #

mplus :: Maybe a -> Maybe a -> Maybe a Source #

MonadPlus IO

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

mzero :: IO a Source #

mplus :: IO a -> IO a -> IO a Source #

MonadPlus Option

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

mzero :: Option a Source #

mplus :: Option a -> Option a -> Option a Source #

MonadPlus STM

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

mzero :: STM a Source #

mplus :: STM a -> STM a -> STM a Source #

MonadPlus ReadPrec

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

MonadPlus ReadP

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

mzero :: ReadP a Source #

mplus :: ReadP a -> ReadP a -> ReadP a Source #

MonadPlus P

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

mzero :: P a Source #

mplus :: P a -> P a -> P a Source #

MonadPlus (Proxy :: Type -> Type)

Since: base-4.9.0.0

Instance details

Defined in Data.Proxy

Methods

mzero :: Proxy a Source #

mplus :: Proxy a -> Proxy a -> Proxy a Source #

MonadPlus f => MonadPlus (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

mzero :: Ap f a Source #

mplus :: Ap f a -> Ap f a -> Ap f a Source #

MonadPlus f => MonadPlus (Alt f)

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

mzero :: Alt f a Source #

mplus :: Alt f a -> Alt f a -> Alt f a Source #

(MonadPlus f, MonadPlus g) => MonadPlus (Product f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

mzero :: Product f g a Source #

mplus :: Product f g a -> Product f g a -> Product f g a Source #

class Applicative m => Monad (m :: Type -> Type) Source #

The Monad class defines the basic operations over a monad, a concept from a branch of mathematics known as category theory. From the perspective of a Haskell programmer, however, it is best to think of a monad as an abstract datatype of actions. Haskell's do expressions provide a convenient syntax for writing monadic expressions.

Instances of Monad should satisfy the following:

Left identity
return a >>= k = k a
Right identity
m >>= return = m
Associativity
m >>= (\x -> k x >>= h) = (m >>= k) >>= h

Furthermore, the Monad and Applicative operations should relate as follows:

The above laws imply:

and that pure and (<*>) satisfy the applicative functor laws.

The instances of Monad for lists, Maybe and IO defined in the Prelude satisfy these laws.

Minimal complete definition

(>>=)

Instances

Instances details
Monad []

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: [a] -> (a -> [b]) -> [b] Source #

(>>) :: [a] -> [b] -> [b] Source #

return :: a -> [a] Source #

Monad Maybe

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: Maybe a -> (a -> Maybe b) -> Maybe b Source #

(>>) :: Maybe a -> Maybe b -> Maybe b Source #

return :: a -> Maybe a Source #

Monad IO

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: IO a -> (a -> IO b) -> IO b Source #

(>>) :: IO a -> IO b -> IO b Source #

return :: a -> IO a Source #

Monad Complex

Since: base-4.9.0.0

Instance details

Defined in Data.Complex

Methods

(>>=) :: Complex a -> (a -> Complex b) -> Complex b Source #

(>>) :: Complex a -> Complex b -> Complex b Source #

return :: a -> Complex a Source #

Monad Min

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Min a -> (a -> Min b) -> Min b Source #

(>>) :: Min a -> Min b -> Min b Source #

return :: a -> Min a Source #

Monad Max

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Max a -> (a -> Max b) -> Max b Source #

(>>) :: Max a -> Max b -> Max b Source #

return :: a -> Max a Source #

Monad First

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: First a -> (a -> First b) -> First b Source #

(>>) :: First a -> First b -> First b Source #

return :: a -> First a Source #

Monad Last

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Last a -> (a -> Last b) -> Last b Source #

(>>) :: Last a -> Last b -> Last b Source #

return :: a -> Last a Source #

Monad Option

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

(>>=) :: Option a -> (a -> Option b) -> Option b Source #

(>>) :: Option a -> Option b -> Option b Source #

return :: a -> Option a Source #

Monad Identity

Since: base-4.8.0.0

Instance details

Defined in Data.Functor.Identity

Methods

(>>=) :: Identity a -> (a -> Identity b) -> Identity b Source #

(>>) :: Identity a -> Identity b -> Identity b Source #

return :: a -> Identity a Source #

Monad STM

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

(>>=) :: STM a -> (a -> STM b) -> STM b Source #

(>>) :: STM a -> STM b -> STM b Source #

return :: a -> STM a Source #

Monad First

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: First a -> (a -> First b) -> First b Source #

(>>) :: First a -> First b -> First b Source #

return :: a -> First a Source #

Monad Last

Since: base-4.8.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: Last a -> (a -> Last b) -> Last b Source #

(>>) :: Last a -> Last b -> Last b Source #

return :: a -> Last a Source #

Monad Dual

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Dual a -> (a -> Dual b) -> Dual b Source #

(>>) :: Dual a -> Dual b -> Dual b Source #

return :: a -> Dual a Source #

Monad Sum

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Sum a -> (a -> Sum b) -> Sum b Source #

(>>) :: Sum a -> Sum b -> Sum b Source #

return :: a -> Sum a Source #

Monad Product

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Product a -> (a -> Product b) -> Product b Source #

(>>) :: Product a -> Product b -> Product b Source #

return :: a -> Product a Source #

Monad ReadPrec

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

(>>=) :: ReadPrec a -> (a -> ReadPrec b) -> ReadPrec b Source #

(>>) :: ReadPrec a -> ReadPrec b -> ReadPrec b Source #

return :: a -> ReadPrec a Source #

Monad ReadP

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

(>>=) :: ReadP a -> (a -> ReadP b) -> ReadP b Source #

(>>) :: ReadP a -> ReadP b -> ReadP b Source #

return :: a -> ReadP a Source #

Monad NonEmpty

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: NonEmpty a -> (a -> NonEmpty b) -> NonEmpty b Source #

(>>) :: NonEmpty a -> NonEmpty b -> NonEmpty b Source #

return :: a -> NonEmpty a Source #

Monad P

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

(>>=) :: P a -> (a -> P b) -> P b Source #

(>>) :: P a -> P b -> P b Source #

return :: a -> P a Source #

Monad (Either e)

Since: base-4.4.0.0

Instance details

Defined in Data.Either

Methods

(>>=) :: Either e a -> (a -> Either e b) -> Either e b Source #

(>>) :: Either e a -> Either e b -> Either e b Source #

return :: a -> Either e a Source #

Monoid a => Monad ((,) a)

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, a0) -> (a0 -> (a, b)) -> (a, b) Source #

(>>) :: (a, a0) -> (a, b) -> (a, b) Source #

return :: a0 -> (a, a0) Source #

Monad (ST s)

Since: base-2.1

Instance details

Defined in GHC.ST

Methods

(>>=) :: ST s a -> (a -> ST s b) -> ST s b Source #

(>>) :: ST s a -> ST s b -> ST s b Source #

return :: a -> ST s a Source #

Monad (ST s)

Since: base-2.1

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

(>>=) :: ST s a -> (a -> ST s b) -> ST s b Source #

(>>) :: ST s a -> ST s b -> ST s b Source #

return :: a -> ST s a Source #

Monad m => Monad (WrappedMonad m)

Since: base-4.7.0.0

Instance details

Defined in Control.Applicative

Methods

(>>=) :: WrappedMonad m a -> (a -> WrappedMonad m b) -> WrappedMonad m b Source #

(>>) :: WrappedMonad m a -> WrappedMonad m b -> WrappedMonad m b Source #

return :: a -> WrappedMonad m a Source #

Monad (Proxy :: Type -> Type)

Since: base-4.7.0.0

Instance details

Defined in Data.Proxy

Methods

(>>=) :: Proxy a -> (a -> Proxy b) -> Proxy b Source #

(>>) :: Proxy a -> Proxy b -> Proxy b Source #

return :: a -> Proxy a Source #

(Monoid a, Monoid b) => Monad ((,,) a b)

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, b, a0) -> (a0 -> (a, b, b0)) -> (a, b, b0) Source #

(>>) :: (a, b, a0) -> (a, b, b0) -> (a, b, b0) Source #

return :: a0 -> (a, b, a0) Source #

Monad f => Monad (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

(>>=) :: Ap f a -> (a -> Ap f b) -> Ap f b Source #

(>>) :: Ap f a -> Ap f b -> Ap f b Source #

return :: a -> Ap f a Source #

Monad f => Monad (Alt f)

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

(>>=) :: Alt f a -> (a -> Alt f b) -> Alt f b Source #

(>>) :: Alt f a -> Alt f b -> Alt f b Source #

return :: a -> Alt f a Source #

Monad ((->) r :: Type -> Type)

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

(>>=) :: (r -> a) -> (a -> r -> b) -> r -> b Source #

(>>) :: (r -> a) -> (r -> b) -> r -> b Source #

return :: a -> r -> a Source #

(Monoid a, Monoid b, Monoid c) => Monad ((,,,) a b c)

Since: base-4.14.0.0

Instance details

Defined in GHC.Base

Methods

(>>=) :: (a, b, c, a0) -> (a0 -> (a, b, c, b0)) -> (a, b, c, b0) Source #

(>>) :: (a, b, c, a0) -> (a, b, c, b0) -> (a, b, c, b0) Source #

return :: a0 -> (a, b, c, a0) Source #

(Monad f, Monad g) => Monad (Product f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

(>>=) :: Product f g a -> (a -> Product f g b) -> Product f g b Source #

(>>) :: Product f g a -> Product f g b -> Product f g b Source #

return :: a -> Product f g a Source #

class Monad m => MonadFail (m :: Type -> Type) Source #

When a value is bound in do-notation, the pattern on the left hand side of <- might not match. In this case, this class provides a function to recover.

A Monad without a MonadFail instance may only be used in conjunction with pattern that always match, such as newtypes, tuples, data types with only a single data constructor, and irrefutable patterns (~pat).

Instances of MonadFail should satisfy the following law: fail s should be a left zero for >>=,

fail s >>= f  =  fail s

If your Monad is also MonadPlus, a popular definition is

fail _ = mzero

Since: base-4.9.0.0

Minimal complete definition

fail

Instances

Instances details
MonadFail []

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> [a] Source #

MonadFail Maybe

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> Maybe a Source #

MonadFail IO

Since: base-4.9.0.0

Instance details

Defined in Control.Monad.Fail

Methods

fail :: String -> IO a Source #

MonadFail ReadPrec

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadPrec

Methods

fail :: String -> ReadPrec a Source #

MonadFail ReadP

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fail :: String -> ReadP a Source #

MonadFail P

Since: base-4.9.0.0

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

fail :: String -> P a Source #

MonadFail (ST s)

Since: base-4.11.0.0

Instance details

Defined in GHC.ST

Methods

fail :: String -> ST s a Source #

MonadFail (ST s)

Since: base-4.10

Instance details

Defined in Control.Monad.ST.Lazy.Imp

Methods

fail :: String -> ST s a Source #

MonadFail f => MonadFail (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

fail :: String -> Ap f a Source #

fail :: MonadFail m => String -> m a Source #

class (Alternative m, Monad m) => MonadPlus (m :: Type -> Type) where Source #

Monads that also support choice and failure.

Minimal complete definition

Nothing

Methods

mzero :: m a Source #

The identity of mplus. It should also satisfy the equations

mzero >>= f  =  mzero
v >> mzero   =  mzero

The default definition is

mzero = empty

mplus :: m a -> m a -> m a Source #

An associative operation. The default definition is

mplus = (<|>)

Instances

Instances details
MonadPlus []

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

mzero :: [a] Source #

mplus :: [a] -> [a] -> [a] Source #

MonadPlus Maybe

Since: base-2.1

Instance details

Defined in GHC.Base

Methods

mzero :: Maybe a Source #

mplus :: Maybe a -> Maybe a -> Maybe a Source #

MonadPlus IO

Since: base-4.9.0.0

Instance details

Defined in GHC.Base

Methods

mzero :: IO a Source #

mplus :: IO a -> IO a -> IO a Source #

MonadPlus Option

Since: base-4.9.0.0

Instance details

Defined in Data.Semigroup

Methods

mzero :: Option a Source #

mplus :: Option a -> Option a -> Option a Source #

MonadPlus STM

Since: base-4.3.0.0

Instance details

Defined in GHC.Conc.Sync

Methods

mzero :: STM a Source #

mplus :: STM a -> STM a -> STM a Source #

MonadPlus ReadPrec

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadPrec

MonadPlus ReadP

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

mzero :: ReadP a Source #

mplus :: ReadP a -> ReadP a -> ReadP a Source #

MonadPlus P

Since: base-2.1

Instance details

Defined in Text.ParserCombinators.ReadP

Methods

mzero :: P a Source #

mplus :: P a -> P a -> P a Source #

MonadPlus (Proxy :: Type -> Type)

Since: base-4.9.0.0

Instance details

Defined in Data.Proxy

Methods

mzero :: Proxy a Source #

mplus :: Proxy a -> Proxy a -> Proxy a Source #

MonadPlus f => MonadPlus (Ap f)

Since: base-4.12.0.0

Instance details

Defined in Data.Monoid

Methods

mzero :: Ap f a Source #

mplus :: Ap f a -> Ap f a -> Ap f a Source #

MonadPlus f => MonadPlus (Alt f)

Since: base-4.8.0.0

Instance details

Defined in Data.Semigroup.Internal

Methods

mzero :: Alt f a Source #

mplus :: Alt f a -> Alt f a -> Alt f a Source #

(MonadPlus f, MonadPlus g) => MonadPlus (Product f g)

Since: base-4.9.0.0

Instance details

Defined in Data.Functor.Product

Methods

mzero :: Product f g a Source #

mplus :: Product f g a -> Product f g a -> Product f g a Source #